Ethnomathematic Exploration Of Minangkabau Batik Tanah “Liek” (Clay Soil Batik) - Isnaniah; M. Imamuddin (CV. AFDIFAL MAJU BERKAH, 2023)
Ethnomathematics in mathematics learning is becoming a trend in Indonesia. Learning mathematics with ethnomathematics is nothing but introducing and learning mathematical concepts through local culture. This research belongs to qualitative research with an ethnographic approach. The purpose of this research is to explore the mathematical concepts found in batik tanah like (clay soil batik). Data in this study were collected by observation, documentation and interviews. Data analysis was carried out with the steps of data reduction, presentation, interpretation, and exposure. The result of this research is that in the motifs of batik tanah